1971
DOI: 10.1126/science.172.3985.859
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Mink to Sheep Scrapie

Abstract: A progressive, fatal spongiform polioencephalopathy was induced in mink intracerebrally inoculated with a suspension of brain from a Suffolk sheep with naturally acquired scrapie. The clinical signs and pathological lesions of the experimental disease were indistinguishable from transmissible mink encephalopathy, a disease of undetermined origin that occurs in mink.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…Although contamination of feed with scrapie-infected sheep parts has been proposed as the cause of TME, the origin of the disease remains elusive. The idea that scrapie in sheep may be a source of TME infection is supported by findings that scrapie-infected mink have a similar distribution of vacuolar pathologic features in the brain and the same clinical signs as mink with natural and experimental TME ( 5 ). However, mink are not susceptible to scrapie infection following oral exposure for up to 4 years postinoculation, which suggests that either the scrapie agent may not be the source of natural TME infection or that only specific strains of the scrapie agent are able to induce TME ( 6 , 7 ) .…”
mentioning
confidence: 98%
“…Although contamination of feed with scrapie-infected sheep parts has been proposed as the cause of TME, the origin of the disease remains elusive. The idea that scrapie in sheep may be a source of TME infection is supported by findings that scrapie-infected mink have a similar distribution of vacuolar pathologic features in the brain and the same clinical signs as mink with natural and experimental TME ( 5 ). However, mink are not susceptible to scrapie infection following oral exposure for up to 4 years postinoculation, which suggests that either the scrapie agent may not be the source of natural TME infection or that only specific strains of the scrapie agent are able to induce TME ( 6 , 7 ) .…”
mentioning
confidence: 98%
“…In the laboratory, the disease has been successfully transmitted to other animals, including mice (2), hamsters (3), mink (4), and, more recently, nonhuman primates (5). The unusual biophysical properties of the scrapie agent and the characteristic neurohistologic changes of scrapie are identical in certain respects with those of transmissible spongiform encephalopathies in humans, such as kuru (6), Creutzfeldt-Jakob disease (7), and some cases of Gerstmann-Straussler syndrome (8).…”
mentioning
confidence: 99%
“…TME was first described by and epidemiological studies indicated that the disease was a foodborne infection caused by an unidentified feed ingredient . Experimental attempts to transmit sheep scrapie to mink from sources in both the United States (Hanson et al, 1971) arid the United Kingdom have been inconsistent with the epidemiology of natural TME (Marsh & Hanson, 1979). In 1985, an outbreak of TME in Stetsonville, Wisconsin, U.S.A. was reported in which fallen dairy cattle were the major animal protein in mink feed (Marsh & Hartsough, 1985;Marsh & Hartsough, 1988;Marsh et al, 1991).…”
Section: Introductionmentioning
confidence: 99%